Enhancement in Farmers’ Income through Scientific Fish Farming – A Case of Farmer FIRST Programme - De, H K; Das, M K; Sivaraman, I; Sahoo, P K; Das, P C; Sarkar, S; Debbarma, J; Swain, S K (Indian Farming, 2021)
Farmer FIRST Programme, an innovative extension approach, focuses on the transfer of advanced technology to the farmers through regular farmers-scientists interface. ICAR-Central Institute of Freshwater Aquaculture, Bhubaneswar has implemented this project in 2016. Needbased training, on-farm demonstration and regular follow ups are the key factors which contributed towards the enhancement of knowledge and skills of the beneficiaries. Average productivity of the adopted ponds rose by 66%. The increased production has also contributed to enhanced per capita fish consumption of the farm families.